The Growing Importance of Mixed-Methods Research in Health - Wasti, Sharada Prasad; Simkhada, Padam; van Teijlingen, Edwin; Sathian, Brijesh; Banerjee, Indrajit (Nepal Journal of Epidemiology, 2022)
This paper illustrates the growing importance of mixed-methods research to a wide range of health disciplines ranging from nursing to epidemiology. Mixed-methods approaches requires not only the skills of the individual quantitative and qualitative methods but also a skill set to bring two methods/datasets/findings together in the most appropriate way. Health researchers need to pay careful attention to the ‘best’ approach to designing, implementing, analysing, integrating both quantitative (number) and qualitative (word) information and writing this up in a way that enhances its applicability and broadens the evidence-based practice. This paper highlights the strengths and weaknesses of mixed-methods approaches as well as some of the common mistakes made by researchers applying mixed-methods for the first time.